PENGARUH STRATEGI PEMBELAJARAN MEROTASI PERTUKARAN PENDAPAT KELOMPOK TIGA ORANG TERHADAP MOTIVASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 14 PALEMBANG - Frederika Yurita; Dewi Koryati; Deskoni Deskoni (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2014)
The problem in this research is whether there are differences in the influence of learning strategy rotates the exchange of opinions of groups of three people with the strategy of learning exchange between groups to motivation learners learn on economic subjects in SMANegeri 14 Palembang? Population in this research is all student of class X SMA Negeri 14 Palembang year lesson 2012/2013 consisting of 6 class with population of 255 students. The sample in this research is taken by using cluster random sampling technique so that X2 class is selected as experiment class and X1 class as control class. Technique of collecting data in this research is questionnaire and observation. Questionnaires are used to collect data on learners' motivation, while observation is used to collect data on the implementation of learning strategies and collect data on learners' motivation. Data analysis technique used to test the hypothesis of t-test. After the hypothesis testing, it can be concluded that there are differences in the influence of learning strategies rotating the exchange of opinions of groups of three people with learning strategies of inter-group exchange on students' learning motivation oneconomic subjects in SMA Negeri 14 Palembang. From this study, it is suggested for teachers to make learning strategies rotate the exchange of opinions of groups of three people as an alternative in the use of learning strategies to improve students' learning motivation on economic subjects.